2021
DOI: 10.3390/coatings11030324
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Therapeutic and Ameliorative Effects of Active Compounds of Combretum molle in the Treatment and Relief from Wounds in a Diabetes Mellitus Experimental Model

Abstract: Foot ulcers are one of the leading causes of severe and high mortality in diabetics. It is known that wound healing in diabetics is a very complicated process due to the direct severe effect of diabetes mellitus on blood vessels, causing difficulty in wound healing. Many methods of treatment have recently been employed for novel dressings for the promotion of tissue regeneration and rapid wound closure. Combretum molle is composed of chemical compounds, such as lignin, gallic acid, and ellagic acid. Twenty mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…In the current study, STG-metal complexes were able to increase the activity of antioxidant enzymes and enhance antioxidant capacity. This antioxidant effect could be attributed to decreasing lipid peroxidation [38]. This finding was in accordance with that of Bao et al [39], who attributed the antioxidant effects of STG due to DPP-4 inhibitors that increase GLP-1 levels, since this effect could be blocked by a GLP-1 receptor antagonist.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, STG-metal complexes were able to increase the activity of antioxidant enzymes and enhance antioxidant capacity. This antioxidant effect could be attributed to decreasing lipid peroxidation [38]. This finding was in accordance with that of Bao et al [39], who attributed the antioxidant effects of STG due to DPP-4 inhibitors that increase GLP-1 levels, since this effect could be blocked by a GLP-1 receptor antagonist.…”
Section: Discussionsupporting
confidence: 89%
“…Oxidative stress is not only a secondary manifestation of diabetes mellitus but also the first cause of a series of complications involved in diabetes mellitus [38]. The present findings agree with this characterization and are supported by our use of novel STG-metal complexes that may present a proper therapeutic approach to prevent the complications of diabetes, wherein we concentrate on early glycemic control and reducing oxidative stress.…”
Section: Discussionsupporting
confidence: 88%
“…Freshly prepared STZ dissolved in phosphate-buffered saline (pH = 4.5) was used to induce diabetes in male rats. STZ (50 mg/kg) (I.P), which was freshly prepared in the early morning, was administered by intraperitoneal injection to male rats that had fasted for 6 h [17] following the administration of high-fat feed (composed of 66.5% commercial feed, 13.5% artificial butter and 20% sugar) for three weeks prior to the experimental induction of DM by a single injection of STZ [18]. Seventy-two hours after STZ injection, blood glucose levels were measured to evaluate the diabetic status of the animals.…”
Section: Experimental Induction Of Dmmentioning
confidence: 99%
“…Hamza et al showed that C. molle inhibited pancreatic, dermal and deoxyribonucleotide (DNA) injury, and thereby improved the oxidative state in male rats, thus suggesting that the use of C. molle extract might be effective in ameliorating hyperglycemia [ 43 ]. Moreover, Hamza et al also recommended the use of C. molle extract as a promising treatment option for patients with severe DFU [ 44 ].…”
Section: Discussionmentioning
confidence: 99%